THE IMPACT OF TOURIZM ON LOCAL CULTURES - Sagatova Muborak Payzidinovna; Quronboyeva Mohinur Mansurbekovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article analyzes the positive and negative impacts of tourism on local cultures. While tourism contributes to economic development, it also significantly affects local traditions, customs, and social life. The study highlights positive aspects such as cultural exchange, preservation of cultural heritage, and community participation, as well as negative factors including the commodification of culture, the demonstration effect, and social conflicts. The findings indicate that the development of sustainable tourism and the active involvement of local communities in decision-making processes can enhance positive impacts and reduce negative consequences.